Pengembangan Konsep Indo-Pasifik: Sebuah Konstruksi Geopolitik Indonesia di Kawasan Melalui ASEAN - Pradipta Nindyan Saputra; Arfin Sudirman (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
Abstract The concept of geopolitics appears to bridge the relationship between geographical factors in contemporary politics. Through its focus on geographical factors, geopolitics has a very materialistic and objective foundation. Based on a critical examination of the implementation of the concept, it becomes clear that the geopolitical framework depends on social construction. Through qualitative methods, this article tries to explain that the concept of